Steady-state pharmacokinetics and metabolism of voriconazole in patients - Geist, Marcus Julian Peter; Egerer, Gerlinde; Burhenne, Jürgen; Riedel, Klaus-Dieter; Weiß, Johanna; Mikus, Gerd (The journal of antimicrobial chemotherapy, 2013)
Voriconazole exhibits non-linear pharmacokinetics in adults and is said to be mainly metabolized by CYP2C19 and CYP3A4 to voriconazole-N-oxide. The aim of this study was to obtain data on steady-state pharmacokinetics after dosing for at least 14 days in patients taking additional medication and in vivo data on metabolites other than voriconazole-N-oxide.Thirty-one patients receiving voriconazole as regular therapeutic drug treatment during hospitalization participated in this prospective study. Pharmacokinetic profiles were obtained for the 12 h (dosing interval) after the first orally administered dose (400 mg) or (if possible and) after an orally administered maintenance dose (200 mg) following intake for at least 14 days (n=14 after first dose; n=23 after maintenance dose). Blood and urine samples were collected and the concentrations of voriconazole and three of its metabolites (the N-oxide, hydroxy-voriconazole and dihydroxy-voriconazole) were determined, as well as the CYP2C19 genotype of the patients. All other drugs taken by the participating patients were evaluated.A high variability of exposure (AUC) after the first dose was slightly reduced during steady-state dosing for voriconazole (82% to 71%) and the N-oxide (86% to 56%), remained high for hydroxy-voriconazole (79%) and even increased for dihydroxy-voriconazole (97% to 127%). In 16 of the 22 steady-state patients, trough plasma concentrations were <2 μg/mL. N-oxide plasma concentrations during steady state stayed almost constant. Hydroxylations of voriconazole seem to be quantitatively more important in its metabolism than N-oxidation.High variability in voriconazole exposure, as well as low steady-state trough plasma concentrations, suggest that the suggested steady-state dosage of 200 mg twice a day has to be increased to prevent disease progression. Therapeutic drug monitoring is probably necessary to optimize the voriconazole dose for individual patients.